Imaginarium - Rosen, Claire (Rocky Nook, 2016)
Imaginarium: The Process Behind the Pictures is a compendium of practical advice and information covering the photographic process--from idea cultivation through execution. The guidance in this book is written with an understanding of the nature of artists at their core and explores the science of how ideas are born, the conditions that facilitate the productive creation of art, and the elements necessary to make creative work. This compendium is applicable across genres, for individual artists and for those working in a commercial capacity. It brings together strategies and tools to help readers generate compelling ideas and create unique images. From the simplest idea to the most fantastical, you will learn brainstorming, concept development, pre-visualization, pre-production, problem solving, and execution steps in the creative process, including practical tools and ideas for overcoming obstacles and achieving success along the way. Contributors: Beth Taubner Mercurylab Alessia Glaviano Vogue Italia Rebecca Manson The Post Office Interviews with: Maggie Steber, Roger Ballen, Sara Lando, Gabriela Iancu, Robin Schwartz, and Eleanor Macnair *** Imaginarium: The Process Behind the Pictures Table of Contents 1: ON ART The Purpose of Art Strong Images Development of an Artist Goals for Making Work Chapter Wrap-Up 2: ARTISTIC LIFESTYLE The Foundation Curation of Experiences Tapping into the Unconscious Creative Psychology Health Nurturing Creativity Community of Artists Chapter Wrap-Up 3: TIME MANAGEMENT Motion Versus Progress Productivity Motivation Work That Fits into Your Life Chapter Wrap-Up 4: PREVISUALIZATION Concept Generation Triggers Divergent Thinking Free Association Brainstorming Mind Mapping Mood Boards Previsualization Concept Development Chapter Wrap-Up 5: PRODUCTION Pre-Production Resources and Research Building a Team Plan B, C, and D On Set Checklist Best Practices Editing Post-Production Chapter Wrap-Up 6: THE VIEWER EXPERIENCE The Viewer Experience Presentation Considerations Critique and Feedback Series and Long-Term Projects Assignments/Commissions Body of Work: What We Leave Behind Chapter Wrap-Up Conclusion Artist Interviews